High-RAP Asphalt Mixtures (>40%): Mechanical Performance, Durability, Sustainability, and Emerging Technologies - Abbas, Saifal (Scientific Journal of Engineering Research, 2025)
Asphalt mixtures that utilize Reclaimed Asphalt Pavement (RAP), particularly at high RAP levels above 40%, are gaining in popularity due to the emphasis on sustainable pavement solutions. This review paper comprehensively evaluates the performance of high RAP asphalt mixtures, focusing on their mechanical characteristics and durability when compared to standard asphalt mixtures. High RAP mixtures perform well in high-traffic scenarios because they have excellent stiffness and resistance to rutting. Still, they have performance limitations that could be remedied through rejuvenators, anti-stripping agents, and premium additives. Durability issues such as moisture susceptibility and long-term aging are investigated, along with the importance of binder blending and rejuvenation on the impacts of aging. The review highlights significant research areas like optimizing rejuvenator formulations, bio-based additives evaluation, and complete life cycle assessments (LCA) to examine the overall sustainability of high-RAP mixtures. The comparison with conventional mixtures highlights high-RAP mixtures' environmental and economic advantages, such as reduced greenhouse gas emissions, decreased energy use, and substantial cost savings. Despite these advantages, variability of RAP content and lack of standard testing are significant challenges. While still in its infancy, new technologies, such as warm-mix asphalt (WMA), and new characterization technologies, such as X-ray computed tomography (CT) and AI, promise to optimize mix design and forecast long-term performance. High-RAP mixes can transform sustainable pavement construction by alleviating these challenges and employing innovative technologies. This article will benefit researchers, engineers, and policymakers looking to facilitate the use of high-RAP mixes in new construction.